2009
DOI: 10.1016/j.chemosphere.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera lectin on development and mortality of Aedes aegypti larvae

Abstract: Aedes aegypti larvae have developed tolerance to many insecticides used for mosquito control. Moringa oleifera seeds contain a water-soluble lectin (WSMoL) and this paper reports the effect of M. oleifera seed extracts (MoE(1-15)) and WSMoL on development and survival of A. aegypti larvae. WSMoL peptide from in-gel trypsin digestion is also described. MoE(1-15) showed hemagglutinating activity and WSMoL had similarity with flocculating proteins from M. oleifera seeds. MoE(1) and MoE(3) delayed larval developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 38 publications
4
92
1
1
Order By: Relevance
“…These results suggest that the active molecule is water soluble and has a low molecular weight (< 12 kDa). Considering that hemagglutination activity was observed in this fraction (Table 1), a strong candidate for ovicidal activity is a flocculation protein from M. oleifera with a molecular mass of 6.5 kDa (GASSENSCHMIDT et al, 1995;NDABIGENGESERE et al, 1995), which has reportedly shown larvicidal activity (COELHO et al, 2009) andovicidal activity against A. aegypti (SANTOS et al, 2012). However, the CENR fraction from M. oleifera showed other protein activities that cannot be ignored, such as hemolysin and protease inhibitors (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the active molecule is water soluble and has a low molecular weight (< 12 kDa). Considering that hemagglutination activity was observed in this fraction (Table 1), a strong candidate for ovicidal activity is a flocculation protein from M. oleifera with a molecular mass of 6.5 kDa (GASSENSCHMIDT et al, 1995;NDABIGENGESERE et al, 1995), which has reportedly shown larvicidal activity (COELHO et al, 2009) andovicidal activity against A. aegypti (SANTOS et al, 2012). However, the CENR fraction from M. oleifera showed other protein activities that cannot be ignored, such as hemolysin and protease inhibitors (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…At work [100] has associated this larvicidal potential with flocculating proteins such as lectins found in the seeds, which delay and/or impede the larvae development of the A. aegypti mosquito and other insects, especially extending larval early stages (L1 and L2). Lectin treatedlarvae in IV instar presented morphological changes as enlarged intestinal lumen and hypertrophy or loss of the luminal epithelium.…”
Section: Larvicidalmentioning
confidence: 99%
“…Lectins have deleterious effects against larvae, developing stages and mature forms of insects from orders Coleoptera, Diptera, Hemiptera, Homoptera, Hymenoptera, Isoptera, Lepidoptera and Neuroptera (Murdock et al, 1990;Eisemann et al, 1994;Powell et al, 1995;Zhu-Salzman et al, 1998;Bandyopadhyay et al, 2001;Isidro et al, 2001;Hogervorst et al, 2006;Kaur et al, 2006;Coelho et al, 2007;Macedo et al, 2007;Fitches et al, 2008;Sá et al, 2008;Coelho et al, 2009;Sá et al, 2009c;Silva et al, 2009;Napoleão et al, 2011;Souza et al, 2011b). Insecticide activity of lectin is generally evaluated by bioassays that incorporate the lectin into artificial diets offered to insects, with insects dying from nutritional deprivation.…”
Section: Insecticidal Activity Of Lectinsmentioning
confidence: 99%
“…Santos et al (2005) revealed the presence of water-soluble M. oleifera lectin (WSMoL) in M. oleifera seed extracts by detection of hemmaglutinating activity. The procedure for WSMoL isolation was defined by Coelho et al (2009) and included the steps of protein extraction with water, precipitation of lectin with ammonium sulfate (60% saturation) and chromatography of precipitated fraction on a chitin column. WSMoL agglutinated human and rabbit erythrocytes in a broad pH range of 4.5 to 9.5 and when kept at 100 ºC for 5 h plus incubation overnight at 37 ºC.…”
Section: Lectins From Moringa Oleifera Seedsmentioning
confidence: 99%